The scientific work of professor N.N. Petrov— an outstanding soviet healthcare organizer, scientist and humanist. Оn the occasion (of the 150th anniversary of his birth) - T. Sh. Morgoshiia; V. A. Tikhonenko; A. V. Kim; M. Azamov; L. A. Rastova; M. S. Trudovsky; A. S. Buneeva; T. S. Kostikova (Clinical Medicine (Russian Journal), 2026)
This article presents the life story of Professor N.N. Petrov, an outstanding surgical oncologist and humanist of his time. Littleknown facts about the scientist are highlighted. Nikolai Nikolaevich was a highly versatile surgeon. The scientist’s universally recognized fame did not come overnight, but through persistent work and quest to resolve complex issues in surgical pathology. It has been noted that his successful resolution of these problems was facilitated not only by his sound training in anatomy and physiology, but also by his desire to work as a pr ac ticin g su rge on an d oncologist in challenging circumstances. He also played a significant role in the creation of the oncology service system in the USSR. In practical work, N.N. Petrov’s successes were facilitated by his natural talent, which developed into brilliant clinical thinking, keen observation, a sensitive and caring attitude toward patients, an ability to understand their psychology, perseverance in helping patients, preserving life at any cost, and a desire to avoid unnecessary risk to the patient. There are individuals whose role in the development of a particular fi eld of science is difficult to overestimate. For Russian oncology, such a figure was Academician N.N. Petrov of the USSR Academy of Medical Sciences. Nikolai Nikolaevich dedicated his entire life to a noble goal — the fight against disease and the alleviation of human suffering. As a true physician and humanist, saving the wounded and helping the sick was always a natural need, a fundamental duty, and a sacred obligation for him.